2015
DOI: 10.4025/actascihealthsci.v37i1.24149
|View full text |Cite
|
Sign up to set email alerts
|

<b>Inflammatory response after session of resistance exercises in untrained volunteers

Abstract: ABSTRACT. The present study aimed to investigate the interaction between the blood cells, inflammatory markers, oxidative stress parameters and delayed onset muscle soreness (DOMS) after a session of resistance exercise (SRE). The sample consisted of sixteen untrained men (26.4±5 years; 25.9±3 kg m -2 ). The SRE was composed of 4 sets of 10 repetitions maximum (extensor bench, squat and leg press) for each exercise. Complete blood cell count, C-reactive protein (CRP), creatine kinase (CK), lipid peroxidation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 25 publications
0
18
1
1
Order By: Relevance
“…However, neither the fight nor the training session resulted in a significant change in the erythrocytes of hematocytes and platelets. Our results were different from those of Teixeira et al (Teixeira et al, 2015) who found that a resistance exercise caused a significant increase in hematocrites, erythrocytes, hemoglobins, and platelets.This can be explained by the fact that in a judo fight, the actions are performed in apnea soliciting, thus, the anaerobic sector in which the low or no use of O2.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, neither the fight nor the training session resulted in a significant change in the erythrocytes of hematocytes and platelets. Our results were different from those of Teixeira et al (Teixeira et al, 2015) who found that a resistance exercise caused a significant increase in hematocrites, erythrocytes, hemoglobins, and platelets.This can be explained by the fact that in a judo fight, the actions are performed in apnea soliciting, thus, the anaerobic sector in which the low or no use of O2.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have found similar results: Callegari et al (Callegari et al, 2017) observed a significant increase in LDH and more pronounced CK levels after resistance exercise with a multiple series protocol. Teixeira et al (Teixeira et al, 2015) showed that a resistance exercise for beginners resulted in muscle damage characterized by an increase in CK. Studies have shown an increase in CK levels following a rugbymatch (Gill, 2006).This increase in CK rate is proportional to the number of tackles (Bauduer et al, 2011) and it is highly correlated with the number of tackles per match (r = 0.922) (Takarada, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOMS was assessed 24 h after the exercise session using a visual analog scale. 7 Total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDLc), glucose, uric acid, urea, and fibrinogen were evaluated using commercial test kits (Lagoa Santa, MG, Brazil). Low-density lipoprotein cholesterol (LDLc) was determined using the Friedewald formula.…”
Section: Data Collection and Biochemical Measurementsmentioning
confidence: 99%
“…2 Oxidation/reduction imbalance 3 occurs during and after REs in high-intensity sessions because the production of reactive oxygen species (ROS) exceeds enzymatic (superoxide dismutase, catalase, and glutathione peroxidase) and nonenzymatic (vitamins A, C , and E, and uric acid) antioxidant capacity, resulting in oxidation of cellular constituents 4,5,6 and an inflammatory response. 3,7 These alterations are clinically characterized by delayed-onset muscle soreness (DOMS), which results in reduced contractility 8 and muscular functionality. 9 Sedentary and/ or untrained individuals are especially vulnerable, 2,9 because DOMS is a transient condition (peak at 24-72 h and symptom resolution in 5-7 days) 10 that may lead to exercise program dropout.…”
Section: Introductionmentioning
confidence: 99%